Association between triglyceride glucose index and risk of cancer: A meta-analysis - Wang, Huan; Yan, Feifei; Cui, Yani; Chen, Feinan; Wang, Guixia; Cui, Weiwei (Frontiers in Endocrinology, 2023)
Background: Triglyceride glucose (TyG) index as a more convenient and reliable predictor of insulin resistance (IR) is thought to be associated with many diseases, but its relationship with cancer remains unclear. Methods: The meta-analysis was conducted to evaluate the effects of TyG index on cancer risk utilizing the available evidence. PubMed, EMBASE, Medline, Cochrane Library and Web of Science were searched from their inception up to July 2022. A random-effects model was used to calculate the effect estimates and 95% confidence intervals (CIs). Results: A total of 6 observational studies met our inclusion criteria, which including 992292 participants. The meta-analysis indicated that the higher TyG index increased cancer risk compared to the lower TyG index group (total effect size =1.14, 95% CI [1.08, 1.20], P<0.001). Conclusions: Our meta-analysis found that the TyG index is related to cancer. More prospective cohort studies and basic research are warranted to verify the relationship.